BAFF, APRIL, and their receptors: physiological role and involvement in the pathogenesis of chronic lymphocytic leukemia - Schab, Katarzyna; Urbańczuk, Magdalena; Urbańczuk, Marcin; Tuzim, Kamila; Tuzim, Tomasz; Lewicki, Marcin (Journal of Education, Health and Sport, 2018)
Chronic lymphocytic leukemia (CLL) is hematopoietic malignancy involving clonal proliferation and accumulation of morphologically mature yet functionally incompetent B-lymphocytes in blood, lymphoid tissue and, less commonly, extralymphatic organs. Despite significant advances in molecular characterization of CLL, the pathogenesis of the disease remains incompletely understood. Besides disturbed apoptosis considered to be the main molecular defect responsible for the development of CLL, some role is also attributed to activation of BCR receptor, triggering of PI3K and MEK/ERK signaling pathways, and activation of nuclear transcription factor κB (NF-κB) which result in increased proliferation of leukemic cells. Intracellular activation pathways may also be triggered by other proteins, including proteins of the TNF family. B cell activating factor (BAFF) and its homolog A proliferation inducing ligand (APRIL) are cytokines of the tumor necrosis factor (TNF) family considered to play the key role in regulation of biological function of B-lymphocytes. Interactions of both molecules with their receptors (BAFF-R, TACI, BCMA) promote survival of normal B-lymphocytes while also affecting their differentiation, maturation, chemotaxis, class switching and antibody production. According to current knowledge, malignant B-lymphocytes responsible for CLL are characterized by upregulation of these proteins and receptors which translates into deregulation of apoptosis and proliferation of cells, higher stage of the disease, and poorer prognosis. This article summarizes current knowledge on the characteristics and physiological importance of BAFF, APRIL and their receptors as well as on the established role of these proteins in the pathogenesis of chronic lymphocytic leukemia including deregulation of leukemic B-lymphocytes together with the potential for BAFF and APRIL proteins being used as prognostic markers in clinical medicine.